(untitled) (Third Sector Social Economic Review, 2026)
This study aims to examine the social, cultural and economic factors determining girls’ participation in education from a social policy perspective.The main objective of the research is to analyze the effects of conceptual frameworks such as equal opportunity,gender inequality and patriarchal structure on girls’ educational processes,using the Halfeti example.The study was conducted in Halfeti,one of the districts in Turkey where regional inequalities are pronounced;the role of local sociocultural dynamics on educational decisions is discussed.A qualitative research method was adopted;the phenomenological model was used. The phenomenological sample consists of women and men aged 18-24 living in Halfeti. Interviews with 15 individuals provide a basis for an in-depth and detailed exploration of the subject. The working group includes 10 female and 5 male participants The findings indicate that girls’ access to education is strongly influenced by structural factors such as family socioeconomic status,traditional gender roles,patriarchal norms,early marriage.In the Halfeti example,it was found that girls’ participation in education decreased significantly,particularly during the transition to secondary education.In conclusion,the study reveals that girls’ participation in education cannot be explained solely by individual or family preferences;holistic,gender-sensitive social policy interventions that take regional characteristics into account are needed.